Design and Development of Scissor Type Car Lifter - Gandhi, Dishant; Dhulugade, Yogesh (Asian Review of Mechanical Engineering, 2018)
Vehicles have always been heavy and requiring regular repairs. That was the necessity behind car lifts’ invention. These days, car lifts are an integral part of many garages and repair shops but it’s applications are not limited to that, they’re also used to raise vehicles for storage in places where ramps are inconvenient or if there are space restrictions. The car lift we are working on is used for raising loaded mini-trucks. The main objective of our project is to design and analyze car lift to fit the given parameters and for doing that, the history and types of car lifts are studied, several research papers are referred to. In case of our lift, it had to be more stable and have a higher capacity so as to lift loaded mini-trucks. The project uses Solid works for design and ANSYS for analysis of the CAD model of the lift. After the design is analyzed, the parts are ordered and the lift is assembled.